If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5n + -4 = 2n + 3n + 6 Reorder the terms: -4 + -5n = 2n + 3n + 6 Reorder the terms: -4 + -5n = 6 + 2n + 3n Combine like terms: 2n + 3n = 5n -4 + -5n = 6 + 5n Solving -4 + -5n = 6 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. -4 + -5n + -5n = 6 + 5n + -5n Combine like terms: -5n + -5n = -10n -4 + -10n = 6 + 5n + -5n Combine like terms: 5n + -5n = 0 -4 + -10n = 6 + 0 -4 + -10n = 6 Add '4' to each side of the equation. -4 + 4 + -10n = 6 + 4 Combine like terms: -4 + 4 = 0 0 + -10n = 6 + 4 -10n = 6 + 4 Combine like terms: 6 + 4 = 10 -10n = 10 Divide each side by '-10'. n = -1 Simplifying n = -1
| 2+3x+5=6x+7-6x | | 9a^2+30a+25/6a^2+a-15 | | 2-2(3x-4)=8-2(5+x) | | 8=p-11 | | a-5=-1+3a | | 3x+5-5=-2x-10 | | -24=-7+x | | 8=14-n | | -10=3x+8+4(x-1) | | 5(2x-1)=3(3x-1) | | 5x-5=3x+10 | | lnx+12x=3.916 | | 3(x+1)=1 | | 3x-8-5x+2=-12 | | 5x-6x-3=0 | | 18/21/4 | | 3x-5y+8=0 | | -5=-z-3 | | 6/7/(-1/3) | | a=b+2b+b-101 | | yu=89 | | m/3=-6 | | 3*a=5*a*8 | | 7.50x/100=617.05 | | x-7.50x/100=617.05 | | 12*17/6 | | 23+x=16 | | 12*7/6 | | f(x)=(x+2)(x-3)-6 | | 5*3/5 | | 4x-8y+12xy=101 | | 4xy+6=8xy-12 |